Development of Total Quality Management Model for Management of International Kindergartens in Bangkok - Krataytong, Aungsiya; Laksana, Sangob (Scholar: Human Sciences, 2016)
The purpose of the study was to develop Total Quality Management model for utilizing the Total Quality Management in managing international kindergartens. The research methodology was a mixed method involving both quantitative and qualitative data collection from content analysis and survey from school administrators. The study investigated the preference of school administrator based on Total Quality Management theory for management of international kindergartens in Bangkok. The study attempted to answer the following questions. (1) what is the management practice in accordance with the Total Quality Management theory; (2) what is the Transformational Leadership for the identification of leadership practices supporting the effective utilization of the Total Quality Management in school management;  (3)what is the preference of school administrator based on Total Quality Management theory for management model of International kindergartens; and (4)what elements would be contained an effective management implementation model for International kindergarten. The result revealed that school administrators approved Total Quality Management is appropriated for international kindergarten management. The findings showed school administrators agreed with five elements which were ranked as the highest mean score which were Total involvement, Process control and improvement, Statistical process control, Evaluation and Education and training for international kindergarten managements areas. The findings also revealed that school administrators agree with the six considerations of Total Quality Management which were ranked as the second highest mean scores, namely, Leadership, Customer focus, Communication, Supportive structure, Reward and recognition and Supplier quality management could reinforce to international kindergarten management areas. Theses Total Quality Management elements can be utilized as a model of the application of Total Quality Management model to effectively support for management areas in international kindergartens in Bangkok.